HUBUNGAN IKLIM KESELAMATAN KERJA TERHADAP SAFETY BEHAVIOR PADA PEKERJA DI PROYEK PEMBANGUNAN REVITALISASI HALTE BRT TRANSJAKARTA PAKET D 15 HALTE - Naviri Agustiani (2023)
Work in the construction sector has high hazards and risks because the work process includes physical work that can cause accidents and occupational diseases. An appropriate safety behavior can prevent work accidents. Work safety behavior can be influenced by the work safety climate. The purpose of this study was to determine the relationship between safety climate and work safety behavior among the workers in the Revitalization Development BRT Transjakarta Package D 15 Shelters Project. This research used quantitative approach with a cross sectional design. Respondents of this study were 76 people selected by total sampling method. Primary data was collected from the NOSACQ-50 questionnaire and safety behavior questionnaire. The results showed that there was a significant relationship between work safety climate and safety behavior in workers (p = 0,001) meanwhile there was no association between, age (p = 1,000), education (p = 0,887), tenure (p = 0,791) and safety behavior. The company can improve the safety climate by conducting safety training for workers to increase their understanding and prioritize safety in the workplace.